Education Challenges and Coping Mechanisms for Artificial Intelligence in Primary and Secondary Schools - Zhao, Xiangqian (Science Insights, 2022)
The application of artificial intelligence (AI) education at the primary and secondary levels has far-reaching implications for the universalization of AI education, the cultivation of AI talent for national growth, and the improvement of student intellectual competency. This article focuses on the history of AI education in China and the challenges it faces in terms of course standards, teaching materials, personnel availability, and instructional strategies. Suggestions for coping tactics include adjusting course standards; creating a scientific textbook structure; expanding the availability of high-quality AI instructors; and promoting fundamental AI education through multi-agency collaboration. It is hoped that this study will help improve how AI is taught in elementary and secondary schools.